APPROACHES TO THE SETTLEMENT OF THE NUCLEAR CRISIS ON THE KOREAN PENINSULA: AN ECONOMIC ASPECT - L. V. Zakharova (Vestnik MGIMO-Universiteta)
A nuclear crisis on the Korean peninsula was primarily caused by security reasons. However, from the very beginning an economic component has been inextricable part of any settlement plan. Since the 1990s the DPRK has been offered economic benefits in return for an agreement to abandon its nuclear program. After the first nuclear test in 2006 the international community led by the USA has emphasized imposing economic restrictions on North Korea. Engagement and sanctions have become two key approaches to dealing with the DPRK. They have been applied simultaneously and separately, unilaterally and multilat¬erally. As a result of the severe economic sanctions imposed against the DPRK by the UN Se¬curity Council the country has been significantly restricted in its external economic relations. Nevertheless, unlike the case of Iran, measures of financial and economic pressure failed to make North Korea abandon its nuclear arsenal, with the escalated tensions between Pyongyang and Washington bringing the region close to war in 2017. In 2018 the situation is dynamically changing as a new stage in the nuclear settlement on the Korean peninsula has begun. The historic USA-DPRK summit held in Singapore on 12 June 2018 opened new opportunities for engaging North Korea. The article revises previous experience and approaches to dealing with the DPRK in the economic sphere with the aim of reducing tensions in the region. Based on the analysis of different strategies applied and positions of the key regional players the author looks at the prospects of using economic methods in the nuclear settlement on the Korean peninsula and also proposes practical measures for economic engagement of the DPRK.